Heart failure related to adult congenital heart disease: prevalence, outcome and risk factors. (7th May 2021) - Arnaert, Stijn; De Meester, Pieter; Troost, Els; Droogne, Walter; Van Aelst, Lucas; Van Cleemput, Johan; Voros, Gabor; Gewillig, Marc; Cools, Bjorn; Moons, Philip; Rega, Filip; Meyns, Bart; et al.
Abstract: Aims: Information on the prevalence, outcome and factors associated with heart failure in patients with adult congenital heart disease (CHD) (ACHD‐HF) is lacking. We aimed at assessing the prevalence and outcome of ACHD‐HF, the variables associated with ACHD‐HF, and the differences between major anatomical/pathophysiological ACHD subgroups. Methods and results: We included 3905 patients (age 35.4 ± 13.2 years) under active follow‐up in our institution (last visit >2010). Outcome of ACHD‐HF cases was compared with sex‐ and age‐matched cases. Univariable and multivariable binary logistic regression with ACHD‐HF diagnosis as a dependent variable was performed. Overall prevalence of ACHD‐HF was 6.4% (mean age 49.5 ± 16.7 years), but was higher in patients with cyanotic CHD (41%), Fontan circulation (30%), and a systemic right ventricle (25%). All‐cause mortality was higher in ACHD‐HF cases when compared with controls (mortality rate ratio 4.67 (2.36–9.27); P = 0.0001). In multivariable logistic regression analysis, age at latest follow‐up [per 10 years; odds ratio (OR) 1.52; 95% confidence interval (CI) 1.31–1.77], infective endocarditis (OR 4.11; 95%CI 1.80–9.38), history of atrial arrhythmia (OR 3.52; 95%CI 2.17–5.74), pacemaker implantation (OR 2.66; 95% CI 1.50–4.72), end‐organ dysfunction (OR 2.41; 95% CI 1.03–5.63), New York Heart Association class (OR 9.28; 95% CI 6.04–14.25), heart rate (per 10 bpm; OR 1.27; 95% CI 1.08–1.50), ventricular dysfunction (OR 3.62; 95% CI 2.54–5.17), and pulmonary hypertension severity (OR 1.66; 95% CI 1.21–2.30) were independently related to the presence of ACHD‐HF. Some variables (age, atrial arrhythmia, pacemaker, New York Heart Association, and ventricular dysfunction) were related to ACHD‐HF in all anatomical/physiological subgroups, whereas others were not. Conclusions: ACHD‐HF is prevalent especially in complex CHD and is associated with poor prognosis. Our data provide insight in the factors related to ACHD‐HF including differences between specific anatomical and physiological subgroups.